The Relevance of Isotherm and Kinetic Models to Chlorophenols Adsorption: A Review - Zaharaddeen N Garba (Hamadan University of Medical Sciences, 2019)
The derivatives of phenols are among the most widely used chemicals in day-to-day life, which lead to water contamination by chlorophenols (CPs). These compounds belong to a class of those widely used chemicals that increase global concern about environmental protection due to their recalcitrant nature. Adsorption process has been employed for the removal of CPs from contaminated water out of many methods of wastewater treatment. This is due to its insensitivity to toxic substances, effectiveness, universal nature, fast kinetics, as well as the ease of operation and its simplicity in the design and applicability. Thus, this study compared the adsorption isotherm models such as linear and nonlinear and well discussed the fundamental characteristics, modelling, and mathematical derivations. Finally, the study highlighted and addressed the role of different isotherm models that were used in describing the adsorptive removal of CPs using various adsorbents.